Transformative Innovations: Harnessing Artificial Intelligence for Sustainable Business Models and Inclusive Economic Development - Treulier, Maxime (Digital Repository of Theses, 2025)
Artificial intelligence (AI) plays a pivotal role in promoting sustainability across diverse industries by improving resource efficiency and reducing waste. This exploration highlights the significance of AI-driven models in product design and lifecycle management, which facilitate the development of products that are more recyclable or reprovable. By adhering to circular economy principles, AI technologies support real-time monitoring of product performance, thereby extending their lifespans and minimizing the need for replacements. The effects of AI adoption differ across sectors; manufacturing industries benefit from automation and quality assurance, while service sectors prioritize enhancing customer interactions. The Chief Artificial Intelligence Officer (CAIO) is instrumental in aligning sustainability goals with organizational strategies. The convergence of AI, big data analytics, and internet technologies empowers small- and medium-sized enterprises (SMEs) to implement sustainable practices effectively. Evidence indicates a positive correlation between AI adoption and enhanced corporate performance, particularly in sustain- ability metrics. As organizations increasingly embrace these technologies, it is crucial to balance innovation with ethical considerations to promote environmental stewardship and achieve sustain- able growth.